2021
DOI: 10.1007/jhep02(2021)014
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to: Generalizing the relativistic quantization condition to include all three-pion isospin channels

Abstract: We have found an error in a statement following eq. (2.5) of our paper, concerning the function f (a, b, k) that first appears in that equation. The issue arises in the statement that it is convenient to take the function f (a, b, k) to be exchange symmetric with respect to its three arguments. This has the unwanted consequence of making six of the seven operators in the column vector of eq. (2.4) identically equal. This, in turn, implies that many operators are identically zero in the definite isospin basis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Simulating quantum systems in finite volume (FV), such as a cubic box with periodic boundary conditions, is a well established theoretical approach to extract information about them, going back to the early work of Lüscher [1,2,3] who showed that the real-world (i.e., infinite-volume) properties of a the system are encoded in how its (discrete) energy levels change as the size of the volume is varied. The method has become a standard approach for example in Lattice Quantum Chromodynamics (LQCD) to extract scattering information for hadronic systems, and extending it in different directions, in particular to three-body systems, is an area of active research [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Moreover, few-body approaches formulated in FV can be used to match and extrapolate LQCD results to an effective field theory (EFT) description [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Simulating quantum systems in finite volume (FV), such as a cubic box with periodic boundary conditions, is a well established theoretical approach to extract information about them, going back to the early work of Lüscher [1,2,3] who showed that the real-world (i.e., infinite-volume) properties of a the system are encoded in how its (discrete) energy levels change as the size of the volume is varied. The method has become a standard approach for example in Lattice Quantum Chromodynamics (LQCD) to extract scattering information for hadronic systems, and extending it in different directions, in particular to three-body systems, is an area of active research [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20]. Moreover, few-body approaches formulated in FV can be used to match and extrapolate LQCD results to an effective field theory (EFT) description [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%